The practising Jamaican scientist - A profile - Hamilton, Marlene A. (1979)
Based on several tests, including ones on science attitude, convergency/divergency, personal adjustment, verbal- spatial-mathematical aptitude, this article presents the patterns emerging from the analysis as a "profile" of the "average" practising Jamaican scientist. Characteristics of this profile include: being the first-born child of a middle-class family, high academic performance throughout school and university, high involvement in and satisfaction with his profession and family life, and well-adjusted personality
Keywords: Scientists